Butterflies of the southern Rocky Mountains area, and their natural history and behavior: photos of mostly eggs larvae pupae. Part II. Papilionidae, Pieridae, Nymphalidae (Libytheinae to Satyrinae) - Scott, James A., author; James A. Scott, publisher (Colorado State University. Libraries, 2020)
These four issues of Papilio (New Series) are photos for my book "Butterflies of the Southern Rocky Mts. Area, and their Natural History and Behavior", (https://hdl.handle.net/10217/200723) showing some adults but mostly early stages (eggs, 1st-stage, mature larvae, and pupae) of as many of the species as possible, primarily from the Southern Rockies area (I added a few other interesting species that do not occur in the area). They have been cropped and downsized to illustrate just the butterflies and conserve kilobytes, rather than serve as artistic images. They are arranged by evolutionary relationship, as in the book text.
Photos of mostly eggs larvae pupae. Part II. Papilionidae, Pieridae, Nymphalidae (Libytheinae to Satyrinae)
Keywords: Papilio. New Series; Butterflies; Lepidoptera